Evaluating woodchip bioreactors for mitigating drainage nitrate levels from a municipal wastewater land treatment site : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Environmental Sciences at Massey University, Palmerston North, New Zealand - Romero Ramírez, Stefanía Yanina (Massey University, 2024)
Woodchips bioreactors are a well-established end-of-drain treatment technology that has been widely used to reduce nitrate (NO₃-) from agricultural drainage water. However, their application to municipal wastewater land treatment sites remains less explored, despite potential advantages. In New Zealand, land application of pre-treated wastewater is a growing practice to mitigate excessive nutrient discharges to the aquatic environment. Land treatment can prove effective when operated correctly, but challenges arise when large volumes of wastewater, and small areas available for irrigation, necessitate high application rates, which can result in NO₃- enrichment of drainage water. The Levin Wastewater Land Treatment Site (LWLTS) is an example of where relatively high annual volumes of municipal wastewater are irrigated over an under-sized application area, resulting in high application depths (4667 mm/year). Consequently, surface drains and shallow groundwater transfer NO₃- to the Waiwiri Stream continually all year. In order to reduce the impact of the LWLTS on the water quality of the Waiwiri Stream, one of its resource consent requirements involves reducing the NO₃- levels in the Waiwiri Stream, downstream from the site. The objective of this thesis was to evaluate the potential use of woodchip bioreactors for reducing NO₃- concentrations in drainage water from LWLTS, including an assessment of the ability of soluble C dosing to enhance NO₃- removal. Initial experiments used small-scale column woodchips bioreactors, which simulated similar water temperatures and NO₃- concentrations to those at the LWLTS. The effect of different water hydraulic retention times (HRT) and the use of dosing with two soluble C sources, liquid sugar, and ethanol, were assessed. Under warm temperature conditions, the column bioreactors achieved 99% NO₃- removal efficiency with a 10-hour HRT. In contrast, under cool water temperatures at the same HRT, the NO₃- removal efficiency decreased to 31%. Soluble C dosing was an effective strategy for enhancing NO₃- removal, with the choice of C source proving to be crucial. Ethanol demonstrated to be more efficient than liquid sugar. Additionally, it was determined that dosing with ethanol at a C:N dosing rate of 1.5:1 achieved high removal efficiencies of 77% under warm conditions and at a 3.3-hour HRT, and 82% under cool conditions and at a 10-hour HRT. Based on the results of the column bioreactor study, the performance of pilot-scale woodchip bioreactors at reducing NO₃- levels in drainage water were evaluated at the LWLTS under field conditions. These experiments involved quantifying the effects of different HRTs and dosing with ethanol at different C:N ratios. Operating the bioreactors, at a 10-hour HRT achieved average NO₃- removal efficiencies of 43% and 59% during the cool and warm seasons, respectively. While, at a 20-hour HRT, the removal efficiencies were 69% and 85%, respectively. The variations in NO₃- removal efficiency between both seasons demonstrated that during the cool season the bioreactors were on average about one-third less effective. When bioreactors, operating at 6.6-hour HRT in cool conditions, were dosed with ethanol at a C:N ratio of 0.75:1, the NO₃- removal efficiency improved from 24% to 93%. This result demonstrates that under field conditions ethanol dosing proved to be a higher effective strategy for enhancing the performance of woodchip bioreactors, particularly during cool periods. Based on the findings of the pilot-scale bioreactors, two woodchip bioreactor designs were proposed for the LWLTS: a non-dosed woodchip bioreactor of 645 m³ operating at a long HRT (20 hours), and an ethanol-dosed woodchip bioreactor of 197 m³ operating at a short HRT (6.6 hours). The two proposed designs provide contrasting approaches, although both are expected to achieve the same annual NO₃- load removal (1174 kg N/year) and have similar annualised NO₃- removal costs ($6.90 and $6.50/kg N, respectively). In the long term, it is expected that the NO₃- removal of the larger non-dosed bioreactor will decline at a faster rate compared to the ethanol-dosed bioreactor due to relying solely of woodchips as the C source. However, it would be less susceptible to the risk of bioclogging and has greater capacity to increase NO₃- removal. In addition, ethanol dosing could be introduced to the larger non-dosed bioreactor in the future, when a decline in NO₃- removal efficiency is observed. Therefore, the overall flexibility of the larger bioreactor design is an advantage but comes with higher initial set-up cost. The results of this research demonstrate that woodchips bioreactors are effective treatment methods for mitigating drain water NO₃- levels at a municipal wastewater land application site. Additionally, C dosing using ethanol proved to be a promising cost-effective alternative to enhance bioreactor performance, allowing the use of relatively short HRTs, especially during cool conditions. This increases the daily volume of water that can be effectively treated.
Keywords: Land treatment of wastewater; Nitrates; Environmental aspects; New Zealand; Sewage disposal plants; Technological innovations; Bioreactors; woodchip bioreactor; drainage water; nitrate; municipal wastewater treatment site; carbon dosing; hydraulic retention time; column experiments; pilot-scale trial; 400410 Wastewater treatment processes